Safety and Tolerability of Accelerated Low-Frequency Repetitive Transcranial Magnetic Stimulation Over the Primary Motor Cortex–A Pilot Study - Engelhardt, Melina; Kimmel, Jana; Raffa, Giovanni; Conti, Alfredo; Picht, Thomas (Frontiers in Neuroscience, 2022)
Low frequency repetitive transcranial magnetic stimulation (rTMS) is capable of inducing changes in the functional organization of underlying brain regions, however often at the cost of long stimulation protocols over several weeks. As these protocols can be difficult to implement in clinical settings, the aim of the present pilot study was to show the feasibility and safety of an accelerated low-frequency rTMS protocol applying multiple sessions daily. To this purpose, nine healthy subjects received 14 sessions of rTMS (1 Hz, 30 minutes, 110% RMT) to the hand motor hotspot. Subjects received stimulation for either 14 days once daily (classical rTMS; c-rTMS), 7 days twice-daily (accelerated rTMS; a-rTMS) or sham stimulation for 14 days once-daily (s-rTMS). Daily stimulation sessions in the a-rTMS group were delivered with a 90-minute break in between. In total, 74% of rTMS sessions in the c-rTMS group, 89% in the a-rTMS group and 98% in the s-rTMS group were free of any side effects. Brief headaches and fatigue in stimulated muscle groups were the most frequent side effects. All side effects were reported to be at maximum mild and of short duration. Thus, accelerated low-frequency rTMS of the motor cortex seems to be a safe and feasible method, previously shown to induce a functional reorganization of the motor system. By shortening treatment duration in days, this approach can potentially make rTMS protocols more accessible to a wider range of patients.